PENGGUNAAN SUMBER BELAJAR BUKU “MUDAH DAN PRAKTIS BELAJAR SHARAF” DALAM MENINGKATKAN KEMAMPUAN BAHASA ARAB SANTRI DI PONDOK PESANTREN DARUL AMAN GOMBARA MAKASSAR - Abu Dzar Al Ghifary Chaer; Nurlaelah; Ishaq Shamad; Hasinuddin Mahmud; Rosmiati; Andi Darmawangsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abu Dzar Al Ghifary Chaer.The Use of the Learning Resource Book “Mudah dan Praktis Belajar Sharaf” in Enhancing Students’ Arabic Language Proficiency at Pondok Pesantren Darul Aman Gombara Makassar (Supervised by Prof. Dr. Hj. Nurlaelah, M.Hum and Dr. H. M. Ishaq Shamad, MA). Sharaf instruction plays a significant role in strengthening students’ Arabic morphological competence within the Islamic boarding school environment. However, Sharaf materials are often perceived as complex and abstract due to the similarity of tashrīf patterns and the systematic demands of word-form transformation. Therefore, the availability of structured and practical learning resources is essential to support effective instruction. Educators are required to select and utilize appropriate learning resources to facilitate comprehension and enhance student engagement in the learning process. This study aims to analyze the process of using the book Mudah dan Praktis Belajar Sharaf as a learning resource in Sharaf instruction at Pondok Pesantren Darul Aman Gombara Makassar. The research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The data analysis techniques included data collection, data reduction, data display, and conclusion drawing. The findings indicate that the book was systematically integrated into both institutional policy and classroom instructional practices. It functioned as the primary reference for presenting tashrīf tables, gradual exercises, and reinforcement of morphological patterns. Teachers also implemented supporting strategies such as song-based memorization methods, quizzes, guided exercises, and group presentations to strengthen students’ understanding. The effectiveness of this learning resource was reflected in increased student participation, improved comprehension of tashrīf patterns, and more structured learning activities. Although several challenges were identified, including limited vocabulary mastery, heterogeneous student abilities, and limited instructional time, overall the use of the book Mudah dan Praktis Belajar Sharaf was considered effective in supporting Sharaf instruction at Pondok Pesantren Darul Aman Gombara Makassar.